Efektivitas Penerapan Metode Gross, Net, Dan Gross Up Dalam Perhitungan Pph Pasal 21 Sebagai Alternatif Terbaik: Studi Kasus di PT ABC - Putri, Intan Badriyah Marantika; Kusuma, Indra Lila; Utami, Wikan Budi (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the effectiveness of three calculation methods for Income Tax Article 21, namely the gross, net, and gross-up methods, in order to identify the best alternative for both companies and employees. A case study was conducted at PT ABC using a descriptive qualitative approach through interviews and analysis of employee salary and tax data. The findings reveal that the gross method reached an effectiveness level of 98.09%, the net method 99.04%, while the gross-up method achieved the highest effectiveness at 100.25%. The novelty of this research lies in its comparative approach, which not only measures tax efficiency but also links it to employee welfare and company tax burdens. The results demonstrate that the gross-up method provides the most effective solution, as it improves employees’ take-home pay while maintaining tax efficiency for the company.